Cyclic isoDGR Peptidomimetics as Low‐Nanomolar αvβ3 Integrin Ligands. Issue 11 (19th February 2013) - Mingozzi, Michele; Dal Corso, Alberto; Marchini, Mattia; Guzzetti, Ileana; Civera, Monica; Piarulli, Umberto; Arosio, Daniela; Belvisi, Laura; Potenza, Donatella; Pignataro, Luca; Gennari, Cesare
<x xml:space="preserve">Abstract</x> A perfect fit: Shown here is the docking best pose of a low‐nanomolar αvβ3 integrin ligand cyclo[DKP‐isoDGR] (atom color tube representation; see figure) into the receptor binding pocket, overlaid on the bound conformation of Cilengitide (green tube representation). The extended isoDGR conformation permits all the important interactions with the extracellular domain of the αvβ3 integrin. The metal ion in the MIDAS region is represented by a magenta sphere.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>